lncRNA HotairM1 Depletion Promotes Self-Renewal of Cancer Stem Cells through HOXA1-Nanog Regulation Loop - Fang Li; Yangfan Xu; Xiaofang Xu; Shengfang Ge; Feifei Zhang; He Zhang; Xianqun Fan (Elsevier, 2020)
In cancer cells, a gain of stemness may have profound implications for tumor initiation, aggressiveness, and clinical outcome. However, the molecular mechanisms underlying the self-renewal maintenance of cancer stem-like cells (CSCs) remain elusive. Here, based on analysis of transcriptome sequencing, we identified a long noncoding RNA (lncRNA) named HotairM1, which is weakly expressed in human colorectal carcinoma and uveal melanoma, and a much lower expression in corresponding CSCs. Our results showed that HotairM1 depletion could promote CSC self-renewal and tumor propagation. Mechanistically, HotairM1 recruit EZH2 and SUZ12 to the promoter of its target gene HOXA1, leading to histone H3K27 trimethylation and epigenetic silencing of HOXA1. The silence of HOXA1 subsequently induces the H3K27 acetylation at the enhancer site of Nanog gene to upregulate its expression. The enrichment of Nanog could further inhibit HOXA1 expression, forming a reciprocal regulation loop augmenting the stemness maintaining effect. In summary, our results revealed a lncRNA-based regulatory loop that sustains self-renewal of CSCs, which highlights the critical role of HotairM1 in CSC development through the HOXA1-Nanog signaling loop.